2014
DOI: 10.1074/jbc.m114.555144
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling and Integrative Modeling Reveal Metabolic Constraints for Carbon Partitioning under Nitrogen Starvation in the Green Algae Haematococcus pluvialis

Abstract: Background:The microalga H. pluvialis shows a distinct pattern of carbon repartitioning upon nitrogen starvation. Results: Data-driven integrative modeling pinpoints metabolic adjustments underlying carbon repartition. Conclusion:In vitro and in silico experiments can dissect the systemic response to nitrogen starvation. Significance: Experimental data in conjunction with integrative modeling enables model-driven hypothesis testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 85 publications
6
50
0
1
Order By: Relevance
“…Indeed, most of the studies carried out with H. pluvialis have been performed in outdoor cultures, using sunlight to induce astaxanthin production. These studies demonstrated that under environmental conditions, mainly in the summer period, and in very high illuminated areas, this microalga can grow and produce astaxanthin [33,34].…”
Section: Light Intensitymentioning
confidence: 99%
“…Indeed, most of the studies carried out with H. pluvialis have been performed in outdoor cultures, using sunlight to induce astaxanthin production. These studies demonstrated that under environmental conditions, mainly in the summer period, and in very high illuminated areas, this microalga can grow and produce astaxanthin [33,34].…”
Section: Light Intensitymentioning
confidence: 99%
“…In 13 C-MFA studies, Monte-Carlo sampling is a well-established way to examine the identifiability of flux distribution and to test the statistical differences of fluxes between different cellular scenarios. While some attempts have been made to implement this technique for FBA-based models (Kleessen et al, 2012;Recht et al, 2014), further advances are needed. This is particularly the case for selecting appropriate context-specific models (from the multitude that may match the high-throughput data) that will become more prominent due to the investigation of interconnected cell type-specific models.…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…2b). The overall increase in TAG under nitrogen deficiency (ÀN) is most likely due to the up expression of de novo FAs biosynthesis, in addition to the conversion of polar lipids (PLs and GLs) into TAG triggered by nitrogen starvation, which has been reported in other green algae (Recht et al, 2014;Xia et al, 2015). A visible increase in relative contents of DAG, MAG and other lipid fractions following an increase of nitrogen supply was also observed.…”
Section: Lipid Composition Related To Culture Conditions and Fatty Amentioning
confidence: 58%
“…in nature habitats, because of photo-bleaching induced by long exposure to high light intensities (Ortega-Morales et al, 2013). The nitrogen deficiency had a significant positive effect on carotenoids accumulation in T. arborum and other species in the same genus (Tan et al, 1993;Abe et al, 1998), which might depend on high expression levels of enzymes involved in de novo b-carotene synthesis, resembling that for Haematococcus pluvialis, under nitrogen deficiency (Recht et al, 2014).…”
Section: Lipid Composition Related To Culture Conditions and Fatty Amentioning
confidence: 99%